Comparative Study of Antenna Designs for RF Energy Harvesting. (24th February 2013) - Shrestha, Sika; Noh, Sun-Kuk; Choi, Dong-You
Abstract : In the last few years, several antenna designs of rectenna that meet various objectives have been proposed for use in RF energy harvesting. Among various antennas, microstrip patch antennas are widely used because of their low profile, light weight, and planar structure. Conventional patch antennas are rectangular or circular in shape, but variations in their basic design are made for different purposes. This paper begins with an explanation and discussion of different designs, put forward with an aim of miniaturization, harmonic rejection, and reconfigurability. Finally, microstrip patch structured rectennas are evaluated and compared with an emphasis on the various methods adopted to obtain a compact rectenna, harmonic rejection functionality, and frequency and polarization selectivity.